tRNA-derived small RNAs in plant response to biotic and abiotic stresses - Wang, Chaojun; Chen, Weiqiang; Aili, Maimaiti; Zhu, Lei; Chen, Yan (Frontiers in Plant Science, 2023)
tRNA-derived small RNAs (tsRNAs) represent a novel category of small non-coding RNAs and serve as a new regulator of gene expression at both transcriptional and post-transcriptional levels. Growing evidence have showed that tsRNAs can be induced by diverse stimuli and regulate stress-responsive target genes, allowing plants to adapt to unfavorable environments. Here, we discuss new developments about the classification and biogenesis of tsRNAs and highlight the expressional regulation and functional roles of tsRNAs in plant biotic and abiotic stress responses. Of note, we also generalized useful bioinformatics tools and resources for tsRNAs study in plant. Finally, we proposed current limitations and future directions for plant tsRNAs research. These recent discoveries have refined our understanding of whether and how tsRNAs enhance plant stress tolerance.